2009
DOI: 10.1007/s00418-009-0624-y
|View full text |Cite
|
Sign up to set email alerts
|

Atypical fast SERCA1a protein expression in slow myofibers and differential S-nitrosylation prevented by exercise during long term bed rest

Abstract: We monitored changes in SERCA isoform speciWc expression and S-nitrosylation in myoWbers of lower limb soleus (SOL) and vastus lateralis (VL) muscle biopsies before and after 60 days of voluntary long term bed rest (BR) without (BR-CTRL group, n = 8) and with exercise countermeasure (BR-EX group, n = 8). Before BR, a typical myoWber type-speciWc distribution of fast and slow SERCA1/2a isoforms was seen. After BR, a subpopulation (approx. 15%) of slow myoWbers in BR-CTRL additionally expressed the fast SERCA1a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…In another study by Talmadge and colleagues [46], it was reported, based on immunohistochemical analyses, that only 9% of MHCI fibers and 3% of MHCIIa fibers from vastus lateralis biopsies taken from healthy adult humans, expressed both SERCA isoforms. High levels of SERCA and MHC mismatch is generally thought of as atypical which can be seen in states of severe muscle disuse such as spinal cord injury [46], bed rest [47] and denervation [7]. Differences in SERCA and MHC isoform expression patterns between our study and previous studies [5,46] are most likely due to analytical differences and/or sensitivity of the specific antibodies that were used, particularly for the detection of SERCA1a.…”
Section: Resultsmentioning
confidence: 58%
“…In another study by Talmadge and colleagues [46], it was reported, based on immunohistochemical analyses, that only 9% of MHCI fibers and 3% of MHCIIa fibers from vastus lateralis biopsies taken from healthy adult humans, expressed both SERCA isoforms. High levels of SERCA and MHC mismatch is generally thought of as atypical which can be seen in states of severe muscle disuse such as spinal cord injury [46], bed rest [47] and denervation [7]. Differences in SERCA and MHC isoform expression patterns between our study and previous studies [5,46] are most likely due to analytical differences and/or sensitivity of the specific antibodies that were used, particularly for the detection of SERCA1a.…”
Section: Resultsmentioning
confidence: 58%
“…PLB and SERCA2a have both been localized to slow muscle fibers, while SERCA1a is mostly expressed in fast muscle fibers 4; PLB is rarely expressed together with both SERCA1a and SERCA2a. However, a small number of “hybrid” fibers expressing both SERCA1a and SERCA2a can be detected in skeletal muscle (1.5%)16, and this percentage is markedly increased in humans by muscle unloading (bed rest) 17. Hybrid fibers are also increased in chronically stimulated fibers 16 or by treatment with β2 agonist 18.…”
Section: Discussionmentioning
confidence: 99%
“…For NOS1 confocal microscopy analysis, immunofluorescence images were obtained by using a three channel confocal laser scanning microscope (Leica TCS SP-2, Leica Microsystems, Bensheim, Germany), as previously described for NOS1-3 isoforms [17]. The relative fluorescence intensity of NOS1 immunostained skeletal muscle structures was measured [18]. Briefly, the area pixel intensity of a selected region of interest (ROI) of type 1 or type 2 fiber was measured in digitized confocal image scans and expressed as arbitrary units (a.…”
Section: Methodsmentioning
confidence: 99%